(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The chemical reactivity of four bis (trimethyltetrathiafulvalenyl) thiophene is determined by its potential (electronic) energy (hyper) surface. All the quantum chemical calculations have been carried out using DFT level of theory, B3LYP functional and 6-31G(d,p) as basis set. Molecular electrostatic potential (MEP) and HOMO-LUMO energy levels have been performed. The local reactivity descriptor such as Fukui function is also performed to determine the reactive sites within the title molecules. The chemometric methods PCA and HCA were employed to find the subset of variables that could correctly classify the compounds according to their reactivity.